Diary. - Arcement, Katherine (London Review of Books, 2013)
The article explores the author's addiction to fan fiction. According to the author, this habit took hold in 2006, not long before the final "Harry Potter" and "Twilight" novels came out, and the year she got a laptop. The author claims fan fiction gave her hours of free entertainment, repetitive strain injury and an introduction to new worlds. The author adds that the world of fan fiction can be found on a few computer servers, including FanFiction.Net.